The Balanced Scorecard - Dinosaur or Giant? - Arne Schulke (IUBH Internationale Hochschule, 2020)
No concept of corporate management has spread as quickly in global business practice as the Balanced Scorecard (BSC) by Robert S. Kaplan and David P. Norton. This discussion paper examines its origins, theoretical foundation, practical distribution and key points of criticism in the literature a quarter of a century after its inception. The paper is based on a former publication by the same author in the German WISU journal.
Keywords: M10; M11; M40; 650; Management Accounting; Controlling; Balanced Scorecard; Management Control